Employees' experiences of personal and collective work-identity in the context of an organizational change - Nordhall, Ola; Hörvallius, Julia; Nedelius, Mathilda; Knez, Igor (Frontiers in Psychology, 2025)
In the present study we investigated employees' experiences of personal and collective work-identity in the context of an organizational change. Data consisted of semi-structured interviews with employees that will be affected by the change. We conducted a theory-driven thematic analysis based on four predetermined main themes: personal and collective emotional, and cognitive work-identity. Respondents experienced distinct and unambiguous proudness, bonding, familiarity and missing in their personal emotional work-identity, and quite distinct and unambiguous coherence, reflection, mental time travel, but ambivalent, or even lack of, correspondence in their personal cognitive work-identity. They experienced a mix of distinct and ambiguous organizational proudness, esteem and affective commitment in their collective emotional work-identity. They experienced distinct and unambiguous identification with the organization, but ambivalent assimilation and incorporation of the organization in their collective cognitive work-identity. Such a complexity in the employees' work-identity experiences also indicates complexity in their organizational change reactions.